Mechano-biochemical marine stimulation of inversion, gastrulation, and endomesoderm specification in multicellular Eukaryota - Nguyen, Ngoc Minh; Merle, Tatiana; Broders-Bondon, Florence; Brunet, Anne-Christine; Battistella, Aude; Land, Emelie Britt Linnea; Sarron, Florian; Jha, Aditya; Gennisson, Jean-Luc; Röttinger, Eric; Fernández-Sánchez, María Elena; Farge, Emmanuel (Frontiers in Cell and Developmental Biology, 2022)
The evolutionary emergence of the primitive gut in Metazoa is one of the decisive events that conditioned the major evolutionary transition having led to the origin of animal development. It is thought to have been induced by the specification of the endomesoderm into the multicellular tissue and its invagination (i.e. gastrulation). However, the biochemical signals underlying the evolutionary emergence of endomesoderm specification and gastrulation remain unknown. Here we find that hydrodynamic mechanical strains, reminiscent of soft marine flow, trigger active tissue invagination/gastrulation or curvature reversal via a Myo-II-dependent mechanotransductive process in both the metazoan Nematostella vectensis (Cnidaria) and the multi-cellular choanoflagellate Choanoeca flexa. In the latter, our data suggest that the curvature reversal is associated to a sensory-behavioral feeding response. Additionally, like in bilaterian animals, gastrulation in the cnidarian Nematostella vectensis is shown to participate to the biochemical specification of the endomesoderm through mechanical activation of the β−catenin pathway via the phosphorylation of Y654-βcat. Choanoflagellates are considered the closest living relative to metazoans, and the common ancestor of choanoflagellates and metazoans dates back at least 700 million years. Therefore, the present findings using these evolutionarily distant species suggest that the primitive emergence of the gut in Metazoa may have been initiated in response to marine mechanical stress already in multicellular pre-Metazoa. The evolutionary transition may have then been achieved by specifying the endomesoderm via a mechanosensitive Y654-β−catenin dependent mechanism, which appeared during early Metazoa evolution and that is specifically conserved in all animals.